2019
DOI: 10.1002/bbb.2019
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergy RES hybrids − assessment of status in Finland, Austria, Germany, and Denmark

Abstract: This paper surveys the status and future prospects of bioenergy renewable energy source (RES) hybrids, i.e. energy conversion processes that have at least two renewable energy inputs, one of which is bioenergy. Finland, Austria, Germany and Denmark were the case study countries. We found that the implementation of bioenergy RES hybrids was already ongoing in various sectors, but a majority of them was focused on domestic heating applications. Bioenergy can be used to provide flexible resources for both energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…They also pointed out that, at present, there is no universal methodology for evaluating flexibility in isolation from the energy system, making feasibility always case-specific, and that the common method to use, LCOE, is not useful for comparing energy generators at widely various capacity factors. 46 In the near future, (1) non-steady-state operation, (2) repeatability, and (3) reduction of the cost of biomass power generation and energy storage systems are critically important factors in addition to considering resource availability, biodiversity, and environmental impacts.…”
Section: Future Research Directions and Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…They also pointed out that, at present, there is no universal methodology for evaluating flexibility in isolation from the energy system, making feasibility always case-specific, and that the common method to use, LCOE, is not useful for comparing energy generators at widely various capacity factors. 46 In the near future, (1) non-steady-state operation, (2) repeatability, and (3) reduction of the cost of biomass power generation and energy storage systems are critically important factors in addition to considering resource availability, biodiversity, and environmental impacts.…”
Section: Future Research Directions and Perspectivesmentioning
confidence: 99%
“…In recent studies, it was reported that biofuel CHP plants with and without energy storage can provide flexibility to balance the intermittency of VRE and power demand. ,,, Table summarizes recent publications on biomass power generation systems combined with VRE. Currently, several methods have been proposed such as a direct solar injection into a gasifier, a preheating of steam or air to a gasifier or to a boiler, preheating HTF to GT, or preheating steam to ST. , Other methods such as preheating of biogas before gasifier, internal combustion (IC) engines combined with PV and secondary batteries, , and a photothermal reactor have also been reported.…”
Section: Biomass Gasification/pyrolysis For Carbon Recycle and Integr...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, bioenergy can be used to provide flexible resources for both energy supply and energy storage. Bioenergy RES hybrids provide the opportunity to optimally switch between distinct sources of energy [30].…”
Section: Electricity Generationmentioning
confidence: 99%